The Periglacial Lake Bretjorna (Ledovoe), Western Svalbard: History of Formation and Recent Sedimentation - N. I. Meshcheriakov; O. V. Kokin; I. S. Usyagina; N. E. Kasatkina (Лëд и снег)
This paper presents the results of geomorphological, geochronological and lithological investigation of a young sedimentation basin – the periglacial Lake Bretjorna (Ledovoe). Formation of the lake began at the end of the first half of the 20th century in the west of Nordenskiöld Land (Western Svalbard) within the marginal zone of the Grönfjord glacier, after significant degradation of this glacial massif. The present-day look of the lake was formed at the end of the 20th century however its geomorphological development went on until the beginning of the 21st. The filling of the sedimentation basin with limnoglacial sediments began approximately from the 1930s and proceeded with spatial and temporal irregularity. Bottom sediments of the lake presented mainly by silty-pelitic material, but in places with an admixture of gravel and pebbles, were formed as the front of the Grenfjord glacier retreated in the direction from north-east to south-west. At the first stage, sediment-genesis was mainly accomplished by the intra- and subglacial sediments, which entered the lake as a result of thermal erosion at the contact of the lake and ice since the late 1940s until the end of the last century, as the present-day lake basin became ice-free. Sediments formed at this stage are composed by coarser and poorly sorted material, which is typical for glacial deposits. At the second stage, the sediments became less coarse and more sorted. After the loss of contact between the lake and the glacier, the role of intra- and subglacial sediments decreased. At this time, sedimentation in the lake goes on by the runoff of melted glacial waters and atmospheric precipitation falling on the catchment area of the lake. The value of the average sedimentation rate in the lake was determined by means of radioisotope dating according to 210Pb and 137Cs and amounted 5.4 mm/year in the north, 12.4 mm/year in the central part, and 16.4 mm/year in the south of the lake, which is comparable with the data obtained by gravity method using sedimentological traps (12–15 mm/year).